MONOXIDE CARBON GAS DILUTION ANALYSIS ON DEVELOPING FACE IN VERTICAL RAISE WITH COMPUTATIONAL FLUID DYNAMICS MODELING USING ANSYS SOFTWARE - Heru Ardiansyah, M
An underground mine air ventilation system design, one must consider the diffusion rate of carbon monoxide gas which is represented by the diffusion coefficient value. This research is expected to be able to analyze the distribution of carbon monoxide gas and analyze the diffusion coefficient value of carbon monoxide gas in raise with similar dimensions in the field using the Ansys Fluent Computational Fluid Dynamics (CFD) simulation. The variable being varied is the duct distance to the face (x), which is 0,25D; 0,5D; 1,5D; and 3D from developing face, the discharge of air flow (Q), which is 0,405 m3/s; 0,324 m3/s; and 0,486 m3/s, as well as the raise model, which is in the form of tubes and beams. Carbon monoxide gas is injected into the inlet from the top of the raise that has been modeled for 10 seconds, then fresh air is injected through the duct from the bottom of the raise that has been made measuring 4 inches for 6 minutes. The decrease in the concentration of carbon monoxide gas is measured at seven predetermined test points. The results of this study indicate that the highest concentration of carbon monoxide gas is located at the observation point a which is closest to the face. There is a correlation between the diffusion coefficient (E) and the airflow rate (Q). The higher the airflow flow rate (Q), the higher the diffusion coefficient (E), but there is no correlation between the diffusion coefficient (E) and the duct-to-face distance (x) is 0.25 D and 0.5D, but the effect is decreasing. the modeling diffusion coefficient (E) as the distance between the duct and face (x) is 1.5D and 3D. In addition, the beam-shaped raise model provides a greater diffusion coefficient (E) value than the tubular raise model.